PENERAPAN PICTURE WORD INDUCTIVE MODEL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS DALAM MENULIS DESCRIPTIVE TEXT - ., Sri Susi Hermawani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The writing learning process which was conducted in the class showed the unsatisfactory result. The test result of writing descriptive text shows very low score. Only 9 students (24%) of 37 students could pass the Minimum Completeness Criteria (KKM) which was set at 70. To overcome this problem, the author tried to apply Picture Word Inductive Model to improve students? learning outcomes especially in writing Descriptive Text. The purpose of this study was to find out whether Picture Word Inductive Model could improve students learning outcomes in writing Descriptive Text of class VII students of SMPN 1 Birem Bayeun the second semester. This study used descriptive analysis technique. The sample of this study were all the seventh grade students of SMPN 1 Birem Bayeun that is 37 students. The technique in collecting data was taken through test, non test, and interview. The result of  cycle I was still unsatisfied because from 37 students only 23 students (62%) achieved the Minimum Completeness Criteria (KKM)with the average score was 67,4.in cycle II there were 33 students (89%) could achieve the Minimum Completeness Criteria (KKM)with the mean was 77,7. The result of this study showed that the application of Picture Word Inductive Model can improve the learning outcomes especially in writing Descriptive Text in Class VII SMPN 1 Birem Bayeun students at the second semester Academic Year of 2017-2018